The effects of online game addiction therapeutic camp on stability of online game addiction model for children and youth in Thailand - Soontawong , Alicha; Viriyapong, Ratchada (Food Agricultural Sciences and Technology, 2018)
Online game addiction is one of the major issues that affects many aspects of child and youth development such as physical development, intelligence, meditation and violent behavior. Due to the fact that there is an increase in the number of addicted gamers every year, this research explored the effects of a therapeutic camp for children and youth who are addicted to online gaming and a support from family to heal, care and give attention to children more closely by constructing and analyzing mathematical model in the form of PATQ Qt p model. The model is studied theoretically and numerically. The basic reproduction number R0 and its sensitivity is calculated. Optimal control model is also constructed. A mathematical program is also used to explore the impact of some parameters on dynamics in specific cases. This is to find some approaches to control the epidemic or reduce number of addicted gamers in Thailand.